Acute pain abdomen in adolescents: a gynecologist’s dilemma - Priya, Sowmya; Arpana, Anju; C., Spandana J.; N., Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Ovarian torsion is 5th most common emergency in gynecology. Benign functional ovarian cysts and benign teratomas are most common among ovarian torsion. Aims and objectives were to study the outcome and HPE of all adolescent girls presenting with acute pain abdomen at BGS GIMS, Bangalore. Methods: A study was conducted at BGS GIMS from 2020 to 2022 of all children and adolescents presenting with acute pain abdomen. Study included data consisting of age, complaints, investigations, intervention and HPE was collected and analysed. Results: There were 21 cases between 12- and 21-years age group who presented with acute pain abdomen in the study period. Majority of them were of 16-19 years age group. Out of 21 cases, 100% of them presented with acute pain abdomen. Operative procedures included 15 (71%) exploratory laparotomy and 6 (29%) operative laparoscopies. Ovarian torsion was seen in 11 cases of which 2 cases had bilateral ovarian torsion and 9 cases had unilateral torsion. Ovarian cystectomy was done in 7 patients, unilateral oophorectomy in 3 patients and unilateral salpingo-oophorectomy in 6 patients. Histopathology reports showed 5 cases of serous cystadenoma, 1 case of teratoma and others were mostly simple cyst or corpus luteal cysts. Conclusions: Acute pain abdomen in adoloscents should be diagnosed early to prevent from risk of ovarian torsions. Operative procedures should aim at fertility preservation.